Health-related quality of life as a predictor of mortality in patients on peritoneal dialysis - Marília Pilotto de Oliveira; Luciana Kusumota; Vanderlei José Haas; Rita de Cássia Helú Mendonça Ribeiro; Sueli Marques; Graziella Allana Serra Alves de Oliveira Oller
Objective: to characterize deaths that occurred, and the association between socio-demographic, clinical, laboratory variables and health-related quality of life and the outcome of death in patients on peritoneal dialysis, over a two year period after an initial assessment. Method: observational, prospective population study with 82 patients on peritoneal dialysis. The instruments used for the first stage of data collection were the mini-mental state examination, a sociodemographic, economic, clinical and laboratory questionnaire and the Kidney Disease and Quality of Life-Short Form. After two years, data for characterization and occurrence of death in the period were collected. The relative risk of death outcome was calculated through statistical analysis; the risk of death was estimated by the survival Kaplan-Meier curve, and determined predictors of death by the Cox Proportional Hazards Model. Results: of the 82 original participants, 23 had as an outcome death within two years. The increased risk for the outcome of death was associated with a lower mean score of health-related quality of life in the physical functioning domain. Conclusion: the worst health-related quality of life in the physical functioning domain, could be considered a predictor of death.